The Simpsons movie - Brooks, James L.; Groening, Matt.; Jean, Al.; Sakai, Richard; Scully, Mike.; Maxtone-Graham, Ian.; Silverman, David, 1957-; Castellaneta, Dan.; Kavner, Julie; Cartwright, Nancy, 1959-; Smith, Yeardley; Azaria, Hank, 1964-; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2007)
Lisa convinces the locals to clean up the polluted Lake Springfield after a crowd of fans sink the Green Day concert stage. Meanwhile, Homer saves a pig from being killed in Krusty Burger and adopts it, calling the animal Spider Pig. After two days, Spider Pig fills up a silo with its excrement and not knowing what else to do, Homer dumps the silo in the lake, polluting it. The angry population forces the Simpsons to move to Alaska.
English track: Dolby digital 5.1; DTS 5.1.
Title from container.
Special features: commentary; directors commentary; deleted scenes and slightly alternate ending; special stuff; trailers.
Editor, John Carnochan ; music, Hans Zimmer.
Dan Castellaneta, Julie Kavner, Nancy Cartwright, Yeardley Smith, Hank Azaria, Harry Shearer, Joe Mantegna, Albert Brooks, Tom Hanks.
MPAA rating: PG-13; for irreverant humor throughout.
Keywords: Simpson, Homer (Fictitious character) -- Drama; Springfield (Imaginary place) -- Drama; Hazardous wastes -- Drama; Offenses against the environment -- Drama; Films for the hearing impaired; Feature films; Animated films; Comedy films